BINARY OPTION PRICING USING LATTICE METHOD - Lesmana, Donny Citra; Christina, Natallia; Kusuma, Ravy Ardian; Nabila, Siti Salwa (PATTIMURA UNIVERSITY, 2025)
One way to minimize risks due to uncertainty in stock price movements is by using derivative products, one of which is an option. Binary options, a type of exotic option, provide a fixed payout if certain conditions are met at maturity, but are difficult to solve analytically. In this study, we utilize binomial and trinomial lattice methods, specifically the Cox-Ross-Rubinstein Binomial, Hull-White Trinomial, and Kamrad-Ritchken Trinomial models, to determine the price of binary options. Results indicate that all three methods converge towards the exact solution, demonstrating their applicability for pricing binary options, with the Kamrad-Ritchken Trinomial method showing superior accuracy due to the lowest mean relative error. Additionally, we analyze factors influencing binary option prices, including initial price, strike price, maturity time, volatility, and risk-free interest rate. The study’s originality lies in the comparative analysis of these methods under the same market conditions. However, limitations include model assumptions and potential data variability that may affect generalizability. Future research could extend these methods to various stock data or other financial instruments to test robustness. This research provides insights into optimal lattice method selection for practitioners in binary option pricing.